Caracterização molecular de genes de resistência às β-lactamases em isolados de chryseobacterium indologenes - Freitas, Ellen Albuquerque de (2017)
Chryseobacterium indologenes is a ubiquitous bacterium related to several types of infections, presenting a multiresistant profile, independent of the isolate clinical sample, reducing the therapeutic options. The aim of this study was to characterize molecularly the resistance genes of β-lactamases in isolates of Chryseobacterium indologenes. This was a descriptive study, in which two multiresistant species of Chryseobacterium indologenes were studied, from the blood culture of two female hospitalized patients, aged over 60 years. Chromosomal and plasmid DNA were extracted and polymerase chain reactions (PCR) were performed to detect ESBL resistance genes (blaTEM, blaSHV, blaAmpC, blaCTX-M groups 1, 2, 8 and 9), carbapenemases (blaGES, blaKPC, blaIMI, blaOXA and blaOXA-48 like) and metallo-β-lactamases, (blaNDM, blaVIM, blaIMP, blaIND-like and blaIND-2). The PCR products were sequenced and later analyzed in the Geneious software program. The blaIND-like gene was detected with similarity to the IND-3 and 8 alleles. In relation to the IND-3 allele, it had a mutation at position 119 (ALA → SER). The phylogenetic tree showed that the BGN 23 isolate presented 100% similarity in relation to the common ancestor and 12% similarity difference in relation to the nearest descendant group, whereas the isolate P133 presented only a 9% difference in relation to its group. As for the common ancestor, the isolate P133 is quite distant, possibly indicating that it has more genetic differences in relation to it. This study detected a mutation at position 119 of the IND-3 allele, not yet described in the literature, which may mean possible changes in the susceptibility profile of the bacterium. The IND-8 allele showed 100% similarity to those already described and inserted in the public Genbank database. In relation to phylogeny, it can be observed that C. indologenes presents as a new lineage inserted along the lineage with Asian and European profile, presenting genetic characteristics in relation to its common ancestor. Molecular studies on bacterial resistance mechanisms of multiresistant species should be continued, as they will aid in future research for the discovery of new drugs, new genetic and/or intrinsic resistance mechanisms, or even the identification of new bacterial molecular targets, in order that the usefulness of the antibiotic therapy can be restored or the introduction of a new antibiotic therapy necessary to treat the infectious diseases caused by them and to avoid the spread of pathogenic clones.